2020
DOI: 10.3390/ijms21207569
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Urinary Extracellular Vesicles from Kidney-Transplanted Patients Treated with Calcineurin Inhibitors

Abstract: Use of immunosuppressive drugs is still unavoidable in kidney-transplanted patients. Since their discovery, calcineurin inhibitors (CNI) have been considered the first-line immunosuppressive agents, in spite of their known nephrotoxicity. Chronic CNI toxicity (CNIT) may lead to kidney fibrosis, a threatening scenario for graft survival. However, there is still controversy regarding CNIT diagnosis, monitoring and therapeutic management, and their specific effects at the molecular level are not fully known. Aimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In addition, the overexpression of C1q subcomponent subunit B and C1r in uEV was strongly correlated with decreased GFR in the first year after kidney transplantation [ 37 ]. During CNI nephrotoxicity, a condition of immunosuppression, the levels of complement factors C3, C5, C7, C9 in uEV of KTR were significantly lower compared to KTR with interstitial fibrosis and tubular atrophy (IFTA), although only 17 KTR were enrolled [ 27 ]. These findings imply that the uEV-complement might be specifically correlated with the host immune response, especially rejection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overexpression of C1q subcomponent subunit B and C1r in uEV was strongly correlated with decreased GFR in the first year after kidney transplantation [ 37 ]. During CNI nephrotoxicity, a condition of immunosuppression, the levels of complement factors C3, C5, C7, C9 in uEV of KTR were significantly lower compared to KTR with interstitial fibrosis and tubular atrophy (IFTA), although only 17 KTR were enrolled [ 27 ]. These findings imply that the uEV-complement might be specifically correlated with the host immune response, especially rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, urine fascin-1 might result from EX released by tubular cells [ 83 ]. Recently, Carreras-Pianella et al [ 84 ] used urinary EVs to investigate the nephrotoxic effects of CNIs and, specifically, their chronic toxicity (CNIT), which can lead to renal fibrosis. The authors enrolled patients treated with CNI who had normal kidney function, suffered from CNIT, or presented interstitial fibrosis and tubular atrophy (IFTA).…”
Section: Clinical Applications Of Proteomics In Kidney Transplantationmentioning
confidence: 99%
“…They observed that the proteome of CNIT was significantly enriched in gene sets related to epithelial cell differentiation, probably because of the death of tubular epithelial cells that forces them to regenerate. A higher expression of cell-linker proteins from the uroplakin and plakin families was also found in CNIT than in IFTA, suggesting a toxic effect by CNI on the urothelium [ 84 ]. These results corroborate the significant roles of EX as a source of pathogenic molecules and non-invasive biomarkers in KT.…”
Section: Clinical Applications Of Proteomics In Kidney Transplantationmentioning
confidence: 99%
“…There were differences in proteomic profiles among renal transplant recipients with normal kidney function, the CNIT group, and the interstitial fibrosis/tubular atrophy (IFTA) group. Proteins of the uroplakin (UPK) and plakin families, including UPK1A, UPK1B, UPK2, UPK3A, envoplakin (EVPL), and periplakin (PPL), were significantly upregulated in the CNIT group, which might have an important role in CNIT processes [ 99 ].…”
Section: Proteomics-based Studies Of Exosomes/sevs For Kidney Diseasesmentioning
confidence: 99%